PERENCANAAN DESAIN INTERIOR PUSAT INFORMASI GEOLOGI BELITUNG TIMUR DENGAN PENERAPAN IDENTITAS BUDAYA LOKAL - Boyke Arief Taufik Firdaus (Jurnal Dimensi Seni Rupa dan Desain, 2022)
This research is an Interior Design Planning process for the Geological Information Center (GIC) Building in East Belitung, which applies the characteristics of East Belitung's cultural identity. This research was motivated by a plan from the Geological Survey Center, Geological Agency of the Ministry of Energy and Mineral Resources in 2019, which was the need for the availability of GIC Buildings and Interiors specifically for the East Belitung district. The facility will later function as an Information Center regarding the diversity of rock types contained in the earth of Belitung, which will become one of the geotourism destinations. The purpose of this research is to produce an Interior design of the East Belitung GIC that applies the cultural characteristics of Belitung, with a form that combines modern style in Modern Facilities with elements of local culture as a distinctive feature. The design process is carried out through an interior design planning approach.